Flipping quantitative tutorials. (September 2018) - Becker, Ralf; Proud, Steven
Abstract: Flipping has become a rather fashionable term in higher education, largely in the format of lecture environments, where students are required to watch introductory material prior to a lecture, but the literature has not discussed flipping in a small class environment. In this paper, we consider statistics and econometrics classes at two UK universities which have introduced flipping to small group teaching. We show that, on the whole, student perceptions are positive towards flipping, and we demonstrate clear, qualitative, pedagogical benefits from flipping the classroom.